Recommendations on renewable energy policies for the GCC countries. (October 2015) - Abdmouleh, Zeineb; Alammari, Rashid A.M.; Gastli, Adel
Abstract: Energy security was the major driver for several countries in the world to opt for alternative sources of energy and reduce CO2 emissions. Being blessed with oil and gas reserves, the situation in the Gulf Cooperation Council (GCC) countries may look different, in a way that investments on Renewable Energy (RE) projects do not create adequate short-term financial returns. However, considering the extreme increase of energy demand locally caused by the industrial and economic development in the region will make seizing the emerging opportunity to develop RE projects a strategic decision. This paper targets regional decision-makers as well as multilateral stakeholders, in an attempt to formulate a set of recommendations on policies to promote RE deployment. It presents the results of the study that covered all GCC countries (Saudi Arabia, United Arab Emirates, Qatar, Kuwait, Bahrain and Oman). The document summarizes GCC countries' RE targets and highlights the main projects and measures established to start this transition. Furthermore, this paper provides an updated and comprehensive overview of the RE situation in the GCC countries, and it includes an assessment of the region's RE potential, current installed RE capacity and project pipeline, institutional and market frameworks. This study analyses the main gaps concerning RE deployment in the region while discussing the financial, fiscal, political, legislative, technological and environmental aspects. Based on that, a set of recommendations is proposed to fill their gaps and help achieving their politically endorsed targets particularly in the electricity sector. The proposed recommendations will help to accelerate the development rate of GCC RE market, support governments' efforts towards fulfilling future RE targets, and overcome potential barriers. However such policies analysis should be carried out individually for each country of the GCC region taking into consideration the specificity of each market and economic strategies with more adapted measures.